Cu-TiO2/SiO2 photocatalysts for concrete-based building materials: Self-cleaning and air de-pollution performance. (27th December 2021) - Khannyra, S.; Mosquera, M.J.; Addou, M.; Gil, M.L.A.
Graphical abstract: Highlights: Cu-TiO2 /SiO2 coatings with self- cleaning and air depollution properties for concrete based building materials. The incorporation of copper increased the performance of TiO2 . Coatings highly adhered to concrete substrates. Durability of coatings was investigated in real-life conditions. Results seem to encourage the use of Cu-TiO2 /SiO2  as coatings for preserving building materials. Abstract: As a consequence of human activities, today, we are exposed to high pollution levels that cause building materials damage and many diseases. The application of TiO2 as coating on building materials has proven the efficiency of self-cleaning and air de-pollution. However, its performance is limited due to its absorption being exclusively located at UV light. In this study, Cu-TiO2 photocatalysts were integrated into silica sol–gel synthesis to manufacture new long-lasting term coatings with self-cleaning and air purification properties for concrete-based building materials. The enhancement of TiO2 photoactivity by incorporating Cu into its network has been clearly demonstrated. The self-cleaning and air de-polluting efficiency were assessed using methylene blue (MB), soot and NO, respectively, indicating that the presence of Cu promotes the TiO2 performance. For low doping levels, by increasing the copper loading, the TiO2 photoactivity increased. The highest efficiency was obtained by the photocatalyst containing 5% copper, which shows maximum destruction of methylene blue and soot of 95% and 50% within 60 min and 168 h of irradiation, respectively. However, higher copper loading led to a decrease in its performance, reaching a total degradation of MB and soot of 90% and 45% after 60 min and 168 h of irradiation, respectively, for the sample containing 15% of copper loading.